The Dynamic Relationship among Domestic Stock Returns Volatility, Oil Prices, Exchange Rate and Macroeconomic Factors of Investment - Shabbir, Malik Shahzad; Said, Laila Refiana; Pelit, Irem; Irmak, Esma (International Journal of Energy Economics and Policy, 2023)
This study investigates the impact of oil price variations, exchange rates, macroeconomic factors and domestic stock volatility in South Asian countries. This study employs a general autoregressive heteroskedastic (GARCH) model using quarterly data from 2001 to 2021. The results reveal that there is a significant relationship between the domestic stock of credit and macroeconomic factors. We find surprising results for the set of the countries; there is a negative impact of asset portfolio investment in the domestic stock for Afghanistan, Bangladesh, India and Pakistan and a positive effect for the remaining countries. There is a positive impact on the economic growth in the majority of countries with the exception of Afghanistan and Bangladesh. Inflation seems to increase while there is an increase in the credit in the economy except for Bangladesh, Bhutan and Nepal. Exchange rate has a negative impact on the domestic stock except for India and Nepal. Further, there is a positive effect on the interest rate spread in Bangladesh, India and Pakistan. Finally, oil prices have a significant impact on exchange rates within the countries’ investments.